Caring for Natural Heritage: Revealing Local Ecological Wisdom in Petilasan Saputangis - Agusta, Fauji (Proceeding International Conference on Religion, Science and Education, 2025)
This research spotlights the existence of indigenous ecological knowledge in Sidamulya Village, Karangpucung District, Cilacap Regency, with a particular interest in the natural environment surrounding the Petilasan Saputangis area. The research explores local customs that reflect environmental respect through rituals and prohibitions that have been observed for centuries. The research is based on an interview with a primary keeper of the petilasan and the community around. Having members of the community take part in activities such as keeping the Petilasan area clean and maintaining the trees denotes a common commitment to the preservation of ecosystems in the surrounding region. It also concentrates on the role key keepers, appointed according to indigenous tradition, play in guiding the conservation imperative. The article considers cooperation and consensus between the community and the key keeper for their interaction to have a positive impact on the maintenance of ecological and cultural harmony. Results of this study have shown that indigenous knowledge may provide a good foundation for managing natural resources on a sustainable basis. This is possibly the knowledge that needs to be included in modern-day conservation policies so as to inspire an integrated approach in environmental conservation.